Analysis of CO2 storage mechanisms at a CO2‐EOR site, Cranfield, Mississippi. Issue 3 (4th January 2018) - Hosseini, Seyyed Abolfazl; Alfi, Masoud; Nicot, Jean‐Philippe; Nuñez‐Lopez, Vanessa
Abstract: Carbon dioxide injected for enhanced oil recovery will partition into several phases in the target geological formation. The distribution into free or residually trapped oil, gas, and brine phases depends on many factors such as reservoir temperature and pressure, initial fluid saturations, brine salinity, and relative permeability parameters, and evolves through time including in the post‐injection period, during which it will tend to stabilize. Our numerical simulations, based on Cranfield, MS CO2 ‐EOR project data, demonstrate that these variations are significant and mostly dependent on the operator's selected field‐development strategy: continuous gas (CO2 ) injection, water alternating gas (WAG) injection, water curtain injection, or combinations thereof. In summary, our work shows that the field development strategy selected by the operator has a major impact on the relative importance of the different trapping mechanisms and that WAG seems to be a promising operational approach to balance both CO2 storage and oil production. © 2018 Society of Chemical Industry and John Wiley & Sons, Ltd.